(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2020)
This contribution aims to present the research of Nicolae Vaschide — a direct pupil of Alfred Binet — by focusing on a set of problems dealing with the mécanisme subconsciente de la pensée and by highlighting the intrinsic bond between the psychological and the physiological nature of the individual. By the same token our research spans the raising interest of that time in image semiotics. The study of his text, Essai sur la Psychologie de la main, which surveys the hand through different analytical approaches (anatomy, artistic morphology, anthropology, psychopathology...) as well as the analysis of his experimental research on chiromancy unveil a dialogue between new psychological paradigms and art history. We will explore how this bond between a still-developing experimental psychology, the use of recording and representational devices of the human body and the use of photographic material foster an original ‘critique scientifique des oeuvres d’art’, fitted to didactic and educational aims, and contributing to the ‘development of the modern seeing’.